Summer sisters ebook A read with jenna pick: a novel. - Blume, Judy (2010)
#1 NEW YORK TIMES BESTSELLER • READ WITH JENNA BOOK CLUB PICK AS FEATURED ON TODAY • “ Summer Sisters is a book to return to again and again.” —Colleen Hoover “As warm as a summer breeze blowing through your hair, as nostalgic as James Taylor singing ‘How Sweet It Is.’ You remember. So does Judy Blume. How sweet it was.”— Chicago Tribune   In the summer of 1977, Victoria Leonard’s world changes forever when Caitlin Somers chooses her as a friend. Dazzling, reckless Caitlin welcomes Vix into the heart of her sprawling, eccentric family, opening doors to a world of unimaginable privilege, sweeping her away to vacations on Martha’s Vineyard, an enchanting place where the two friends become “summer sisters.”   Now, years later, Vix is working in New York City. Caitlin is getting married on the Vineyard. And the early magic of their long, complicated friendship has faded. But Caitlin begs Vix to come to her wedding, to be her maid of honor. And Vix knows that she will go—because she wants to understand what happened during that last shattering summer. And, after all these years, she needs to know why her best friend—her summer sister—still has the power to break her heart.